O imprevisto previsível: uma revisão acerca da relação entre a saúde dos metroviários de São Paulo e o ambiente de trabalho - Junqueira, Bárbara Haddad (2020)
Due to its large extension and the vast number of users, the Companhia do Metropolitano de São Paulo (Metrô) – the subway company at São Paulo, Brazil – is often the scene of accidents that can cause fatalities and that may represent additional risks to the workers’ mental health. In view of this context, this study, based on an integrative literature review, aimed to understand the factors that affect the health of Metrô train drivers. Academic articles and papers, in English and Portuguese that specifically addressed topics related to the physical and psychological health of these workers were considered. Of 78 publications found from the expanded initial descriptors, 18 studies met inclusion criteria. The analysis of those works led to the conclusion that critical situations that promote psychological stress are part of the daily life of employees. In relation to the work organization, inadequate shifts, excessive bureaucracy and lack of autonomy, control over the work and recognition seem to be factors that contribute to the activity being perceived as stressful, with the consequent impacts on psychic health. Added to these aspects are specific issues of work on the subway network, such as confrontations with those users who are reckless, that disrespect safety rules and limits, and, even more seriously, the situations of running over, resulting from the fall of passengers on the rails, by accident or due to suicide attempts. In those cases, given the anonymity of the victims and the lack of a link between them and the drivers, the concept of vicarious grief is useful to understand the trauma experienced by the professionals who witness the tragedy. There is evidence, however, that the support and care offered by the company in these circumstances are insufficient. On the other hand, articles show an advance in the production of knowledge on workers’ mental health, even though they have revealed little about intervention and care initiatives aimed at preventing illness and help professionals who witness serious accidents. Therefore, it is clear the importance and the need to carry out studies that deal with the promotion and prevention of mental health of those who, due to their activities, need to face potentially traumatic situations